Cellular, Molecular, and Clinical Aspects of Allergic Disorders 1979
DOI: 10.1007/978-1-4684-0988-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Basophils and Mast Cells: Structure, Function, and Role in Hypersensitivity

Abstract: httroductionSeveral important discoveries of the past few decades have launched a renaissance of research into basophil and mast cell function. These include the discovery of IgE and its affinity for basophils and mast cells and the demonstration of the ability of these cells to elaborate and release not only histamine but also a variety of lowmolecular-weight mediators of immediate hypersensitivity. Moreover, the application of modern methods of tissue fixation and processing has permitted confident identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 240 publications
1
13
0
Order By: Relevance
“…The relationship of mast ceils to basophils has been widely discussed (12). Basophils are bone marrow-derived granulocytes that normally circulate in the blood and, unlike mast 442 THE JOURNAL OF CELL BIOLOGY • VOLUME 95, 1982 cells, are not ordinarily found in connective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of mast ceils to basophils has been widely discussed (12). Basophils are bone marrow-derived granulocytes that normally circulate in the blood and, unlike mast 442 THE JOURNAL OF CELL BIOLOGY • VOLUME 95, 1982 cells, are not ordinarily found in connective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating histamine-containing, IgE receptor-bearing cell characterized in humans and guinea pigs is the basophil (26,27). Several early studies failed to identify basophillike cells in mouse blood (28)(29)(30), but recent investigations have reported basophils with a few metachromatic granules in mouse blood (31,32) RMCP, rat mast cell protease.…”
Section: Introductionmentioning
confidence: 99%
“…The cultured cells depend on the T-cell lymphokine interleukin 3 for growth (23) and contain an oversulfated chondroitin sulfate proteoglycan, termed chondroitin sulfate E proteoglycan (24). The cultured interleukin 3-dependent mast cell and the mouse connective tissue mast cell, which contains primarily heparin proteoglycans (24), can be distinguished by differential reactivities with a panel of monoclonal antibodies (25).The circulating histamine-containing, IgE receptor-bearing cell characterized in humans and guinea pigs is the basophil (26,27). Several early studies failed to identify basophillike cells in mouse blood (28)(29)(30), but recent investigations have reported basophils with a few metachromatic granules in mouse blood (31,32) RMCP, rat mast cell protease.…”
mentioning
confidence: 99%
“…The relative role of various anti gens of human filarial worm provoking allergic responses is not well known. Many pathogenic mechanisms related to the development of allergic responses are both of type I and type IV variety [5], and information regarding these phenomena in filariasis is not available. In the present study it has been shown that IgE responses, as seen by the ability of serum to release histamine from mast cell after antigenic challenge, developed 4 months after infection.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations range from filarial fever with lymphangitis and lymphadenitis during the acute phase to elephantiasis, hydrocele, and chyluria during the chronic phase of infection. Yet another manifestation is tropical pulmonary eosinophilia [2], These clinical symptoms are closely related to the diversity of the host immune re sponse to the parasite [3], Mast cell infiltration of various tissues and elevation of serum IgE levels are associated with many helminthic infections [4], The mast cells medi ate both immediate and delayed T cell dependent immu nological reactions [5]. Lymphatic filariasis might also be linked with the formation of parasite-specific IgE and re lease of histamine from sensitized mast cells [6], Because the role of parasite antigens in allergic reac tions of filariasis is poorly understood, in the present study we attempted to investigate the response of mast cells to wards defined filarial antigens of adult Brugia malayi un der in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%